The Role of Parents in Improving the Nutritional Status of Early Childhood - Intan Arum Anjar Wati; ‎ Zulhijriani; Sholihah Gustavia Yolanda (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Background: Parents play a key role in supporting optimal growth and development in toddlers, particularly in preventing malnutrition. Methods: This study employed a qualitative design with a single case study approach. Data were collected through in-depth one-on-one interviews with 10 participants selected using purposive homogeneous sampling. Data analysis was conducted using explanation building techniques. Data validity was ensured through the criteria of credibility, transferability, dependability, and confirmability. Results: The findings revealed 7 themes and 15 sub-themes. Parents' roles included regular attendance at integrated health posts (Posyandu), appropriate parenting practices, and provision of balanced nutrition. Mothers received support from their husbands and extended family members. Health workers contributed through health education (KIE), Posyandu services, and supplementary feeding. Barriers faced included limited parental time and difficulty feeding children. Cultural practices, such as traditional massage, also influenced child care. Parents expressed hope for the sustainability of the program and improvement in children's nutritional status. Conclusion: Effective reduction in toddler nutritional status requires synergy between parents, families, and health workers, while addressing existing challenges and supporting community expectations for sustainable interventions.